PEMANFAATAN PERASAN BUAH KEPEL (Stelechocarpus burahol (Blume) Hook & Thomson) SEBAGAI ANTISEPTIK LUKA - Prasojo Pribadi; Elmiawati Latifah; Rohmayanti Rohmayanti (Universitas Ahmad Dahlan, 2014)
Fruit of kepel known contain of saponin and flavonoid, fruit of kepel is a plant that hasantibacterial and antiinflamation activity. This research purposed for made juice of fruit kepeland test of open wound healing process activity. Juice of fruit kepel is made with variety ofconcentration, which 20%, 40%, 60%, and 80%. Negative control used aquadest and positivecontrol used BetadineÂ® (Povidon Iodine). This type of research is experimental research,procedure start from the preparation of test materials, first identifying plants, then make fruitjuice of kepel and divide into several concentration, followed by grouping into six group of testanimals. All quantitative data were statistically analyzed using Anaylsis of Variance (Anova)and continued with Tukey Test, The lowest activity on the negative control and increase on thegroup of juice with concentration 20%, 40%, 80%, and 60%, higher activity on the positivecontrol. With wound healing broad parameters result that the group fruit juice of kepelconcentration 60% and 80% showed the statistically analyzed was more significant (p<0.05) 178 PharmaÒ«iana, Vol. 4, No. 2, 2014: 177-183than the negative control. So it can be taken conclusion that fruit juice of kepel concentration60% and 80% having wound healing activity.